Precision analysis based on Cramer–Rao bound for 2D acoustics and electromagnetic inverse scattering. (19th May 2015) - Diong, M L; Roueff, A; Lasaygues, P; Litman, A
Abstract: The aim of the present article is to predict the expected precision quantitatively in inverse scattering when one tries to determine the intrinsic properties of a given target from its scattered field. To conduct such a study, we analyze the precision of contrast estimators with the Cramer–Rao bound (CRB) when the target is homogeneous, infinitely-long and with a circular cross-section and with an additive complex circular gaussian noise at the receivers. An unified framework is derived to handle acoustic or electromagnetic imaging configurations equally. Numerical tests enable to quantitatively appraise the variations of the CRB with respect to the considered physical situation parameters: transmission/reflexion, antennas arrangement, weak/strong scatterers, noise level and source frequency. These analyzes are performed with respect to the real and imaginary parts of the contrast.